Rasmussen Encephalitis with Delayed Seizure Onset - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Two children, ages 6 and 7 years, with progressive hemiparesis and radiological and histopathological confirmation of Rasmussen encephalitis (RE) had no seizures or epileptic EEG activity until 6 to 7 months after onset of symptoms, in a report from Bikur Cholim Hospital, Jerusalem, Israel.